Analisis Bibliometrik Tax Avoidance - Ainiyah, Nur; Bahril Ilmiddaviq, Muhammad; Setiono, Hari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
The enormous benefits of taxes for the country and the tendency of taxpayers to engage in tax avoidance and even tax evasion has attracted researchers to explore and reveal important information related to taxes such as understanding taxpayer behavior, efforts to form effective tax policies as well as transparency and accountability. financial reports related to taxes. Its challenging for researchers who’ll research tax avoidance because there are still obstacles, mainly related to legal gaps, data limitations and the global dimension. This research aims to provide analysis related to tax avoidance research for the 2019-2024 using VOS Viewer software. This study conducting a systematic literature review, using a bibliometric analysis. The results show that the research trend with the Tax Avoidance theme has decreased from 2019 to 2024 due to research turning to issues related to the Covid-19 pandemic, the emergence of tax harmonization regulations and the government's efforts to reduce tax avoidance practices and access to sensitive data. and difficult to obtain. The relationships that occur are divided into 5 clusters. The first cluster include 6 items, the second 3 items, the third 2 items, the fourth 2 items, and the fifth only 1 item. Tax avoidance has brightness and at the same time has large dots in its high visualization, while the other 13 items have faded colors and at the same time have small dots in their visualization. Thus, there have been many studies using tax avoidance items in their research and the other items are still rare, this condition made opportunities to conduct research on the theme of tax avoidance by combining other variables/items that are already visible in the visualization or hasn`t visible yet.